Exploration of Parents’ Involvement in Their Children’s Education - Obafemi, Kayode Ezecheal; Obafemi, Taiye Olayinka; Sulaimon, Jamiu Temitope; Yakubu, Francis Moodu (Bumi Publikasi Nusantara, 2023)
This study explored parents’ involvement in their children’s education in Ilorin West Local Government Area of Kwara State, Nigeria. A descriptive research design was adopted. A total of 216 parents were selected using a multi-stage sampling technique. Validated and reliably tested research instrument using Questionnaire on Parents’ Involvement in their Children’s Education (QPICE) was used. The reliability index of QPICE (r = 0.78) was determined using the test-retest method. One research question and one hypothesis were raised and formulated respectively to guide the study. Data were analyzed using percentage, mean, and t-test. The findings of the study revealed that the level of parents’ involvement in their children’s education was low. Also, there was a significant difference in parents’ involvement in their children’s education based on gender. It was concluded that the level of parents’ involvement in their children’s education was low. The study recommended that parents should be more involved in their children’s education